Dengue and Dengue Virus in Guangdong, China, 1978–2017: Epidemiology, Seroprevalence, Evolution, and Policies - Cui, Fengfu; He, Feiwu; Huang, Xiaorong; Tian, Lina; Li, Saiqiang; Liang, Chumin; Zeng, Lilian; Lin, Huifang; Su, Juan; Liu, Liping; Zhao, Wei; Sun, Limei; et al. (Frontiers in Medicine, 2022)
Background Guangdong is a hyper-epidemic area of dengue, which has over 0.72 million cumulative cases within the last four decades, accounting for more than 90% of cases in China. Local epidemic of dengue in Guangdong are suspected to be triggered by imported cases and result in consequent seasonal transmission. However,the comprehensive epidemiological characteristics of dengue in Guangdong are still unclear. Methods The epidemiology, seroprevalence, molecular evolution of dengue virus and the development of policies and strategies on prevention and control of dengue were analyzed in Guangdong, China from 1978 to 2017. Findings Seasonal transmission of dengue virus in Guangdong, China was mainly sustained from July to October of each year. August to September was the highest risk periods of local dengue outbreaks. Most of dengue cases in Guangdong were young and middle-aged adults. Five hundred and three fatal cases were recorded, whereas declined within the last two decades (n=10). Serological test of healthy donors' serum samples showed a positive rate of 5.77%. Dengue virus 1-4 (DENV 1-4) were detected in Guangdong from 1978 to 2017. DENV 1 was the dominant serotype of dengue outbreaks from 1978 to 2017, with an increasing tendency of DENV 2 since 2010. Local outbreaks of DENV 3 were rare. DENV 4 was only encountered in imported cases in Guangdong, China. The imported cases were the main source of outbreaks of DENV 1-2. Early detection, management of dengue cases and precise vector control were the key strategies for local dengue prevention and control in Guangdong, China. Interpretation Dengue has not become an endemic arboviral disease in Guangdong, China. Early detection, case management and implementation of precise control strategies are key findings for preventing local dengue transmission, which may serve for countries still struggling to combat imported dengue in west pacific areas.